Pelatihan Pembuatan Biobriket sebagai Upaya Penguatan Jiwa Kewirausahaan Berbasis Energi Terbarukan - Alaydrus, Ali Zainal Abidin; Selfiyah, Selfiyah (LPPPM STAI Darul Hikmah Bangkalan, 2025)
The issue of energy scarcity and organic wast management represents both a challenge and an opportunity in advancing environmentally friendly renewable energy. As part of the younger generation, university students have significant potential to serve as agents of change in developing innovative solutions, particularly in entrepreneurship based on alternative energy. This activity aimed to equip students of Universitas Kutai Kartanegara (Unikarta) through outreach and training on producing briquettes from organic waste as an effort to strengthen entrepreneurial capacity. The methods included theoretical instruction on briquette production and its business prospects, technical demonstrations, and interactive discussions on alternative energy–based business opportunities. The results indicate an improvement in students’ understanding and skills in converting waste into energy, as reflected in the increase in the average score from 73.75 (pretest) to 98.33 (posttest), representing a 33.3% improvement. This program is expected to serve as an initial stimulus for cultivating environmentally conscious young entrepreneurs capable of addressing future energy sustainability challenges